Efektivitas Tiga Sumber Mikro Organisme Lokal (MOL) Terhadap Intensitas Serangan Penyakit Moler pada Bawang Merah (Allium ascalonicum L.) - Nisa Kamilah; Salamiah Salamiah; Muhammad Indar Pramudi (www.ulm.ac.id, 2023)
This research aims to determine the effectiveness of three sources of Local Micro Organisms (MOL) on the intensity of moler disease attacks on shallot plants in peatlands. This study used a one-factor Completely Randomized Design (CRD) method consisting of 4 treatments and 5 replications, namely t0 = without administration of MOL (control), t1 = MOL of 10% leri water, t2 = MOL of leri water + 10% banana stem and t3 = MOL of water + 10% fish waste. The results of observations of the incubation period for moler disease for the first symptoms to appear were 14 days after inoculation (HSI). The percentage of moler disease is not influenced by the source of MOL. The highest percentage was shown in shallot plants that were not applied with MOL (71.43%). Meanwhile, the lowest percentage was found in shallot plants which were applied with MOL sources from water mixed with fish waste. This treatment also produced the highest number of tubers, namely 130,000 tubers/ha (356.11 kg/ha). Meanwhile, the largest tuber diameter was produced by plants that were applied with MOL leri water combined with banana stems.